2021
DOI: 10.1101/2021.03.19.21253425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Vaccine Perceptions in New York State’s Intellectual and Developmental Disabilities Community

Abstract: Background: People with intellectual and developmental disabilities (IDD) are at disproportionate risk for severe COVID 19 outcomes, particularly those living in congregate care settings. Yet, there is limited data on vaccine perceptions in the disability community. Objective: To explore COVID 19 vaccine perceptions in individuals with IDD, their family members, and those who work with them, to inform a statewide vaccine information and messaging project. Methods: A national survey, adapted for the IDD communi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Studies including disability have largely been narrow in geographic scope (i.e. New York state 13 ) or based on medical diagnoses as an indicator of disability (i.e. multiple sclerosis 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies including disability have largely been narrow in geographic scope (i.e. New York state 13 ) or based on medical diagnoses as an indicator of disability (i.e. multiple sclerosis 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…We could find only one study with any data from people with ID themselves. In a survey of family carers, paid staff, and people with intellectual and developmental disabilities in New York State, USA, Iadarola et al (2021) reported data on vaccine willingness from 91 people with disabilities (including people with ID). 'Vaccine intent' was defined as definitely or probably being willing to have the vaccine and included a small number of people who had already had a vaccine, with 83.5% reporting positive vaccine intent.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 26 papers were selected and analysed, focusing on the socio-demographical predictors of vaccine willingness and the attitudes that inspire vaccine hesitancy in healthcare workers. Only two papers were found that focussed on healthcare workers working with individuals with intellectual disabilities (Iadarola et al, 2021;Lunsky et al, 2021). Vaccine willingness percentages were comparable between the respondents of these two papers and within the subgroups of these papers.…”
Section: Discussion Ijns Manuscript Template (August 2021)mentioning
confidence: 92%
“…In the two papers that describe vaccine hesitancy in healthcare workers that care for people with intellectual disabilities (Iadarola et al, 2021;Lunsky et al, 2021), the main socio-demographical predictor of willingness was age, with younger people being more hesitant for vaccination. Other sociodemographical characteristics like profession, gender, ethnicity, education and geographical location were not statistically significant predictors of vaccine willingness.…”
Section: Discussion Ijns Manuscript Template (August 2021)mentioning
confidence: 99%
See 1 more Smart Citation